Transformasi Digital Dalam Agribisnis: Pemanfaatan Artificial Intelligence (Ai) Untuk Optimalisasi Produksi Dan Pemasaran Ubi Singkong Di Desa Mulya Jaya, Kabupaten Tulang Bawang Barat - Nyoman Indra; Putu Yudy Wijaya (Journal Research of Management, 2025)
The development of artificial intelligence (AI) technology presents significant opportunities for modernizing the agricultural sector, including in cassava cultivation and marketing. However, in Mulya Jaya Village, West Tulang Bawang Regency, the use of AI by farmers remains very limited. This study aims to describe the actual conditions of cassava production and marketing and evaluate the potential for AI applications to support increased efficiency and farmer welfare. This research was conducted using a qualitative descriptive method, involving interviews, direct field observations, and a review of various literature sources. The results indicate that most farmers still rely on traditional methods for farming and selling their crops through middlemen. Farmers' low understanding of digital technology, coupled with limited supporting facilities and the unavailability of artificial intelligence systems suited to local conditions, are major challenges in the process of agricultural digitalization. However, significant opportunities remain for implementing innovations such as plant disease detection applications, sensor-based weather and soil moisture monitoring tools, and the use of digital platforms for marketing activities. Therefore, this research encourages the implementation of technology training for farmers, the development of software tailored to local needs, and synergy between the government, educational institutions, and digital agricultural business actors to accelerate the realization of modern, inclusive, and sustainable village agriculture.